Réponses

2013-05-12T19:19:42+02:00

Bonjour

A = 1/4 ((a+b)²-(a-b)² ]

1) pour a = 1  et b = 5  

A = 1/4 [(1+5)²-(1-5)² ]

A = 1/4 [ 6² -(-4)² ]

A = 1/4 ( 36 - 16)

A = 1/4 * 20 = 5

2)  pour a = -2  et b  = -3

A = 1/4 [(-2-3)² - (-2+3)² ]

A = 1/4 [(-5)² - 1² ]

A = 1/4 (25 - 1)

A = 1/4 * 24 = 6

3=

A = 1/4 [(a+b)² - (a-b)² ]     

on voit l'identité remarquable a² - b² = (a-b)(a+b)    où a = (a+b)   et b = (a-b) 

A = 1/4 [ ( a+b-a+b)(a+b+a-b) ]

A = 1/4 ( 2b * 2a) ]

A = 1/4 ( 4 ab ) 

A = ab 

donc il a raison